PENGARUH PEMBERIAN DONGENG DENGAN BONEKA TANGAN TERHADAP KEMAMPUAN BERBAHASA INDONESIA - Sulisworo Kusdiyati (Fakultas Psikologi, Universitas Islam Negeri (UIN) Sunan Gunung Djati Bandung, 2010)
The purpose of this study was to obtain empirical data about the effect of fairy telling style with Hand Puppet towards children’s ability of Indonesian Language from low socioeconomic status at class B At Taufik kindergarten in Bandung. The population in this study are all class B students of At Taufik Kindergarten with the characteristic ages 5-6 years (preschool age), the students who received treatment come from families with low socioeconomic status, students with average level of intelligence, the first time following the activities of fairy tales with hand puppets at At Taufik kindergarten. The research method used was quasi experimental design with pretest-Group One-posttest design, while the statistical techniques used were t-test (t-test). The result obtained t count = -13.336, t table with α = 0.05 and df = 15: 1.76. It means that the provision of fairy tales with hand puppets have an impact on the ability of Indonesian language skills of children from low socioeconomic status in kindergarten B At Taufiq in Bandung.